Reactions to Smoke-free Policies and Messaging Strategies in Support and Opposition: A Comparison of Southerners and Non-Southerners in the US - Berg, Carla J. (Health Behav Policy Rev, 2015)
OBJECTIVES: We explored differences in support for smoke-free policies among Southerners versus non-Southerners within a quota-based non-probability sample of adults in the United States. METHODS: In 2013, a cross-sectional online survey was conducted among 2501 adults assessing tobacco use, reactions to personal and public smoke-free policies, and persuasiveness of various message frames regarding smoke-free bar/restaurant policies. RESULTS: Southerners were no different from non-Southerners in support for most public and private smoke-free policies. The most effective pro-policy messages regarded hospitality, health, and individual rights/responsibilities; the most persuasive anti-policy messages involved individual rights/responsibilities. Compared to non-Southerners, Southerners rated pro-policy messages involving economic impact, religion/morality, and hospitality as more persuasive. CONCLUSIONS: Factors other than public opinion accounting for lagging policy adoption must be explored.